Genome-Wide Identification and Expression Profiling of the TCP Family Genes in Spike and Grain Development of Wheat (Triticum aestivum L.) - Zhao, Junmin; Zhai, Zhiwen; Li, Yanan; Geng, Shuaifeng; Song, Gaoyuan; Guan, Jiantao; Jia, Meiling; Wang, Fang; Sun, Guoliang; Feng, Nan; Kong, Xingchen; Chen, Liang; et al. (Frontiers in Plant Science, 2018)
The TCP family genes are plant-specific transcription factors and play important roles in plant development. TCPs have been evolutionarily and functionally studied in several plants. Although common wheat (Triticum aestivum L.) is a major staple crop worldwide, no systematic analysis of TCPs in this important crop has been conducted. Here, we performed a genome-wide survey in wheat and found 66 TCP genes that belonged to 22 homoeologous groups. We then mapped these genes on wheat chromosomes and found that several TCP genes were duplicated in wheat including the ortholog of the maize TEOSINTE BRANCHED 1. Expression study using both RT-PCR and in situ hybridization assay showed that most wheat TCP genes were expressed throughout development of young spike and immature seed. Cis-acting element survey along promoter regions suggests that sub-functionalization may have occurred for homoeologous genes. Moreover, protein-protein interaction experiments of three TCP proteins showed that they can form either homodimers or heterodimers. Finally, we characterized two TaTCP9 mutants from tetraploid wheat. Each of these two mutant lines contained a premature stop codon in the A subgenome homoeolog that was dominantly expressed over the B subgenome homoeolog. We observed that mutation caused increased spike and grain lengths. Together, our analysis of the wheat TCP gene family provides a start point for further functional study of these important transcription factors in wheat.